Anatomical analysis of abdominoplasty - Filipe Vidica Teodoro Barcelos; Luiz Eduardo Toledo Avelar; Leonardo Santos Bordoni; Raul Vidica Teodoro Barcelos (Revista Brasileira de Cirurgia Plástica)
Abdominoplasty is a common surgical procedure in plastic surgery. Consequently, several technical variations have been created with the aim of reducing complications and obtaining better results in the abdominal contour. The anatomy of the abdominal region plays an important role in this procedure, since arguments in favor of techniques, such as classic abdominoplasty and lipoabdominoplasty are linked to anatomical principles. This highlights the plastic surgeon's need to have a good knowledge of the anatomy of this region. Not only will this knowledge enable plastic surgeons to understand the reasons for adopting certain surgical procedures, but it will also enable them adapt these procedures to the anatomical characteristics of each patient. In addition, this knowledge will help determine the morphological changes caused by surgery. Therefore, this study aimed to identify studies in the literature focusing on the anatomical description of both classical abdominoplasty and other variants, such as lipoabdominoplasty. It also aimed to discover the anatomical and physiopathological explanations for the major inherent surgical complications.